Interconnection of Religion and Culture in the Multicultural Education in Indonesia - Anis, Ahmad; Miftah, Muhammad; Manshur, Ali; Nadiyya, Ahsanu (Universitas Pendidikan Ganesha, 2024)
The failure of education in shaping character is often caused by social, economic, political, cultural, religious, and moral inequalities, resulting in social disharmony. This study aims to determine the relationship between religion, culture, and education. This type of research is qualitative research through a literature study approach with analytical techniques through data reduction, data presentation, and descriptive data conclusions from various literature. The object of this study is religion and culture, including definitions, types, elements and relationships between religion and culture. While the subject of this research is educational institutions in Indonesia in multicultural education through various literature. The results of this study show that religion and culture have important values in education. Each has a strong relationship with education. Thus, the implications of this study are expected that Indonesian people realize the importance of religion in education because it is able to strengthen faith, creed, and morals. The importance of culture in education makes humans have life guidelines and obey norms or rules. This research can also increase awareness and appreciation of religious and cultural diversity among students, teachers, and other education stakeholders.